ANALYZING PRONOUNS IN “A FRESH N FRUITY SPRING” STORY BOOK BY LAUREN CECIL - Sari, Rekno (English Education:Journal of English Teaching and Research, 2019)
English is interesting. In learning English, we start from learning the basic things. A part of Speech is the basic aspect in English. Pronouns is parts of speech. By knowing pronouns, a person can make simple sentence. It can be used to master vocabulary and to motivate someone to be fluently in English. The title of this research is an analyzing pronoun in “A Fresh N Fruity Spring” story book by Lauren Cecil. The aim of this research is to find out the pronouns in a story book, in order to be master in vocabulary and making simple sentence from it. The method which will be applied in this research is a descriptive qualitative. Key words: parts of speech, pronoun, story book